Population health management in France: specifying population groups through the DRG system - A. Malone; S. Gomez; S. Finkel; D. Chourchoulis; E. Morcos; M. A. Loko; T. Gaches; D. Laplanche; S. Sanchez (BMC, 2021)
Abstract Background Population health management (PHM) by hospital groups is not yet defined nor implemented in France. However, in 2019, the French Hospitals Federation launched a pilot program to experiment PHM in five territories around five Territorial Hospital Groups (GHT's). In order to implement PHM, it is necessary to firstly define the population which healthcare facilities (hospitals) have responsibility for. In the French healthcare system, mapping of health territories however relies mainly on administrative data criteria which do not fit with the actual implementation of GHT's. Mapping for the creation of territorial hospital groups (GHTs) also did not include medical criteria nor all healthcare offers particularly in private hospitals and primary care services, who are not legally part of GHT's but are major healthcare providers. The objective of this study was to define the French population groups for PHM per hospital group. Methods A database study based on DRG (acute care, post-acute and rehabilitation, psychiatry and home care) from the French National Hospitals Database was conducted. Data included all hospital stays from 1 January 2016 to 31 December 2017. The main outcome of this study was to create mutually exclusive territories that would reflect an accurate national healthcare service consumption. A six-step method was implemented using automated analysis reviewed manually by national experts. Results In total, 2840 healthcare facilities, 5571 geographical zones and 31,441,506 hospital stays were identified and collated from the database. In total, 132 GHTs were included and there were 72 zones (1.3%) allocated to a different GHTs. Furthermore, 200 zones were manually reviewed with 33 zones allocated to another GHT. Only one area did not have a population superior to 50,000 inhabitants. Three were shown to have a population superior to 2 million. Conclusions Our study demonstrated a feasible methodology to define the French population under the responsibility of 132 hospital groups validated by a national group of experts.